Akad Mudharabah dalam Fiqh Mualamah Kontemporer Study Literatur Hasil Penelitian di Indonesia - Fadhilla Husna; Mutia Febrina Sari; Taufik Ramadhan SY; H. Aidil Alfin (Pusat Riset dan Inovasi Nasional, 2025)
Mudharabah contract is a form of economic cooperation in Islam that involves capital owners (shahibul maal) and managers (mudharib). In the contemporary context, the application of this contract has developed along with the dynamics of the modern economy, especially in the Islamic financial sector. This article is a literature study that aims to analyze the understanding and application of the mudharabah contract in the perspective of contemporary fiqh, by referring to various classical and modern literature, as well as fatwas of international and national Islamic financial institutions.